KEGIATAN PENYULUHAN BUANG SAMPAH SEMBARANGAN DI SD NEGERI 101826 DESA TUNTUNGAN II - Putri, Deviani Arianti; Riska, Ananda; Puan Maulida Syifa, Rizqi; Putri Aulia, Ramadhani; Refiana, Revail; Lea, Salshabilla April; Salsabila, Audina; Yusnidar Sari, Mutiara; Rapotan, Hasibuan (Jurnal Pengabdian Masyarakat Kesehatan Indonesia, 2024)
One of the common and increasingly frequent problems faced by developing countries is poor waste management. This waste problem is also one of the crucial problems facing Indonesia. This is also compounded by the fact that public awareness is still lacking regarding waste management and the dangers of environmental waste. This research was carried out at SD Negeri 101826 Tuntungan II on Saturday, 18-25 May 2024. This research is qualitative research using observation, interviews, question and answer and games methods involving various parties as respondents. The aim of this research is so that students at SD Negeri 101826 Tuntungan II can understand and apply knowledge regarding the differences between organic waste and non-organic waste in order to make it easier to dispose of and process waste in accordance with the correct waste disposal criteria. The benefit of this research is that it is a form of caring for the school environment and protecting the earth from waste that is difficult to decompose, so that it can minimize littering. By carrying out several stages and explaining about waste, we can immediately give an example to children that it is important for us to protect schools from various diseases that can result if waste is thrown away carelessly.